1999
DOI: 10.1074/jbc.274.35.24503
|View full text |Cite
|
Sign up to set email alerts
|

α-Oxidation of Fatty Acids in Higher Plants

Abstract: A previously studied system for ␣-oxidation in cucumber was re-examined using the newly developed techniques and was found to catalyze the same conversions as those observed with the recombinant enzymes, i.e. enzymatic ␣-dioxygenation of fatty acids into 2(R)-hydroperoxides and a first order, non-stereoselective degradation of hydroperoxides into ␣-oxidation products. It was concluded that the recombinant enzymes from tobacco and Arabidopsis were both ␣-dioxygenases, and that members of this new class of enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
78
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(82 citation statements)
references
References 48 publications
(66 reference statements)
4
78
0
Order By: Relevance
“…In algae as well as in higher plants (5), it has been reported that a long-chain fatty aldehyde would be formed through decarboxylation of the corresponding 2-hydroperoxy fatty acid (Scheme 1). 2-Hydroperoxy fatty acids are chemically unstable and have a half-life time of ϳ30 min in an aqueous buffer at 23°C (11). Thus, to detect the unstable fatty acid 2-hydroperoxide, the fatty acid as a substrate was incubated with the purified enzyme on ice and the product was immediately esterified with ADAM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In algae as well as in higher plants (5), it has been reported that a long-chain fatty aldehyde would be formed through decarboxylation of the corresponding 2-hydroperoxy fatty acid (Scheme 1). 2-Hydroperoxy fatty acids are chemically unstable and have a half-life time of ϳ30 min in an aqueous buffer at 23°C (11). Thus, to detect the unstable fatty acid 2-hydroperoxide, the fatty acid as a substrate was incubated with the purified enzyme on ice and the product was immediately esterified with ADAM.…”
Section: Resultsmentioning
confidence: 99%
“…The protein derived from the gene was expressed in insect cells and found to cause uptake of molecular oxygen in the presence of polyunsaturated fatty acids such as linoleic, linolenic, and arachidonic acids. Later, the protein was identified as fatty acid ␣-oxygenase, which catalyzes the conversion of linoleic acid and the other fatty acids into the corresponding (R)-2-hydroperoxy fatty acids (11). Interestingly, the primary structures of plant ␣-oxygenases show similarity with those of mammalian PGHSs, although the substrates and products of these two oxygenases are quite different from each other.…”
mentioning
confidence: 99%
“…Aliphatic shortand medium-chain aldehydes and alcohols are emitted by various plant parts and are probably formed by enzymatic reduction of the parent acyl CoAs (Flamini et al, 2007). Alternatively, alcohols can also be formed by ADH-mediated hydrogenation of aldehydes, and medium-chain aldehydes are intermediates of the a-oxidation cycle starting with common fatty acids (Hamberg et al, 1999). However, alcohols are less important as flavor molecules due to their high odor thresholds in comparison with their aldehyde homologues.…”
Section: Fatty Acid-derived and Other Lipophylic Flavor Compoundsmentioning
confidence: 99%
“…PIOX belongs to a larger family of heme-containing proteins that oxygenate fatty acids (4), which include the mammalian cyclooxygenases (COX-1 and COX-2; (5)), linoleate diol synthase (LDS) from the fungus Gaeumannomyces graminis (6, 7), and a Pseudomonas alcalignes protein of unknown function encoded by OrfX (8). PIOX has also been identified in many plant species, including Nicotiana attenuata (9), Nicotiana tabacum (3), Arabidopsis thaliana (3, 10), O. sativa (11), Capsicum annuum (12), and Lycopersicon esculentum (13).PIOX utilizes stereoselective oxygenation to convert linoleic acid (LA) (18:2, n-6) and other fatty acid substrates to their corresponding 2R-hydroperoxides, generating a novel class of oxylipins (3,11,14,15). The resulting 2R-hydroperoxides undergo spontaneous decarboxylation to shorter aldehydes and fatty acids (11,14).…”
mentioning
confidence: 99%